2012
DOI: 10.1115/1.4005978
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Film Cooling Unsteadiness on Turbine Blade Leading Edge Heat Flux

Abstract: Film cooling in the hot gas path of a gas turbine engine can protect components from the high temperature main flow, but it generally increases the heat transfer coefficient h partially offsetting the benefits in reduced adiabatic wall temperature. We are thus interested in adiabatic effectiveness η and h which are combined in a formulation called net heat flux reduction (NHFR). Unsteadiness in coolant flow may arise due to inherent unsteadiness in the external flow or be intentionally introduced for flow cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The coolant hole inlet boundary condition was modeled to have a turbulence intensity of Tu = 1% and a length scale of Λ / d = 0.42. These turbulence characteristics are similar to the turbulence levels of the wind tunnel on which the computational model was based [10].…”
Section: Fig 1 Coordinate System and Hole Geometrysupporting
confidence: 58%
See 2 more Smart Citations
“…The coolant hole inlet boundary condition was modeled to have a turbulence intensity of Tu = 1% and a length scale of Λ / d = 0.42. These turbulence characteristics are similar to the turbulence levels of the wind tunnel on which the computational model was based [10].…”
Section: Fig 1 Coordinate System and Hole Geometrysupporting
confidence: 58%
“…6 shows the  results spanwise averaged over the region -3.93 ≤ y/d ≤ 3.93 (similar to a case with a pitch spacing of 7.86 d between the holes) compared to the corresponding cases using the experimental methodology on an identical geometry and described in Ref. 10. The spanwise averaged CFD data shown in Fig.…”
Section: Grid Convergencementioning
confidence: 95%
See 1 more Smart Citation
“…In contrary, Ekkad et al 13 reported through measurements that pulsed jet enhanced by lowering heat transfer coefficient as compared to steady jet, while considering a leading-edge model with a single film cooling hole. Heat flux measurements by Rutledge et al 14 also elucidated that the net heat flux was normally increased by pulsed film cooling. However, it could be advantageous at higher blowing ratio beyond the optimum value of its steady operation.…”
Section: Introductionmentioning
confidence: 97%
“…Rutledge and King [10] conducted a computational study to determine how the coolant pulse affects film cooling performance in LE region, and they thought that the poor performance of pulsed cooling occurs because the jet necessarily spends some time operating at an inefficient blowing rate. Then Rutledge et al [11] experimentally investigated net heat flux reduction (NHFR) on semicircular cylinder simulating the LE of a turbine blade, and found that for moderate BRs, a steady film flow yields better NHFR, while for higher coolant flow rates beyond the optimum BR, pulsed film cooling is better.…”
Section: Introductionmentioning
confidence: 98%